2014
DOI: 10.1002/ejsp.2036
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to climate change‐related ingroup norms: Do dimensions of group identification matter?

Abstract: Recent research provides evidence that group norms influence intentions to engage in pro‐climate behaviour and that identification with the group moderates the norm effects. However, past studies have neglected to examine if the effects on norm adherence vary among different identification aspects. The present studies close this gap by investigating group‐level self‐investment (i.e. the importance of and satisfaction with the group) and self‐definition (i.e. perceived similarities among group members) as possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(66 citation statements)
references
References 35 publications
4
60
2
Order By: Relevance
“…Maybe not surprisingly, individuals do not mechanically adhere to ingroup norms when they cognitively self‐categorize as group members but have to balance personal‐level goals with group‐level goals (Blanton & Christie, ; Crane & Platow, ). This is also in line with research suggesting that conformity to ingroup norms is not so much a “cold” inference process but seems to be the product of affect and motivation related to the ingroup (Masson & Fritsche, ). However, extending past research (e.g., Packer, ), our findings also provide first evidence that membership status may represent an important boundary condition for the translation of high self‐investment into loyal deviance (although we do not preclude complementary explanations of our findings).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Maybe not surprisingly, individuals do not mechanically adhere to ingroup norms when they cognitively self‐categorize as group members but have to balance personal‐level goals with group‐level goals (Blanton & Christie, ; Crane & Platow, ). This is also in line with research suggesting that conformity to ingroup norms is not so much a “cold” inference process but seems to be the product of affect and motivation related to the ingroup (Masson & Fritsche, ). However, extending past research (e.g., Packer, ), our findings also provide first evidence that membership status may represent an important boundary condition for the translation of high self‐investment into loyal deviance (although we do not preclude complementary explanations of our findings).…”
Section: Discussionsupporting
confidence: 90%
“…The scale had been translated into German by a back‐translation procedure. Due to space limitations, we reduced the number of items from 10 to seven (Masson & Fritsche, ). Perceived peripheral group membership (i.e., low ingroup protoypicality) was assessed with three items (“I have not much in common with other students of my university.”, “All in all, I am not a typical student of my university.”; seven‐point scale from 1 = “strongly disagree” to 7 = “strongly agree”; “How much do you differ from other students?”; seven‐point scale from 1 = “differ not at all” to 7 = “differ very much”).…”
Section: Methodsmentioning
confidence: 99%
“…Given the centrality of sustainability for Californian identity, it is perhaps unsurprising that the other messages revealed similar results-when norms are highly legitimised, they increase the correspondence between personal and in-group identities. Indeed, Masson and Fritsche ( 2014 ) found that highly self-invested participants reported stronger climate-friendly intentions as a function of sustainable group norms, particularly for challenging climate-friendly behaviours.…”
Section: Social Identity Perspectivesmentioning
confidence: 99%
“…Blackwood and Louis () showed that two aspects of self‐investment—group centrality and group solidarity—predicted collective action intentions of anti‐war activists. Thus, there is initial evidence that self‐investment is a potentially stronger predictor of behavioral outcomes than self‐definition, which reflects the mere acknowledgment of group membership and similarity (Masson & Fritsche, ; see also Leach et al, ).…”
Section: Multidimensionality Of Ingroup Identificationmentioning
confidence: 99%